PENGARUH SELF-REGULATED LEARNING TERHADAP HASIL PRETEST AKM NUMERASI SISWA DI SEKOLAH PENEMPATAN KAMPUS MENGAJAR - Zahra Fajrianti; Dani Firmansyah (IKIP Siliwangi, 2023)
The purpose of this research was to determine the effect of self-regulated learning on the results of the numeracy AKM pretest at school was choice by teaching campus batch 4. The population of this research is class VIII students of SMP Islam Karawang for the 2022/2023 academic year. The sample was selected using a simple random sampling technique so that 14 students of class VIII-B were obtained. Data collection was carried out using AKM test and self-regulated learning questionnaires which were then analyzed using simple linear regression analysis, namely by conducting normality tests and data linearity test first as prerequisites with the help of SPSS software version 25 for windows. The results showed that the absence of a positive influence of self-regulated learning on the results of the numeracy AKM pretest of students. This is evidenced by the value of Sig. = 0.869 0.05 then it was H0 accepted so that the variable (X) self-regulated learning did not have a positive effect on the variable (Y) of the numeracy AKM pretest result.